Optimal gestational weight gain in women with pregestational type 2 diabetes: a population-based cohort study in China - Xue, Yiwei; Cui, Zifeng; Shu, Xinyu; Juan, Juan; Kang, Xin; Yao, Mi; Chen, Xu; Wei, Zhuo; Kong, Lingyi; Chen, Haitian; Cui, Shihong; Gao, Fengchun; et al. (Diabetology and metabolic syndrome, 2025)
The global prevalence of pregestational type 2 diabetes mellitus (T2DM) has increased concurrently with increasing rates of overweight and obesity. Effective weight management during pregnancy is critically associated with maternal and neonatal outcomes. However, no universally accepted guidelines for gestational weight gain (GWG) in high-risk pregnancies with T2DM currently exist. A nationwide, multicenter cohort of 2078 T2DM pregnancies was analyzed, categorizing GWG based on latest Chinese guidelines. Multivariate regression analyses were performed to evaluate the impact of GWG deviations on adverse pregnancy outcomes. Interquartile range (IQR) analysis and restricted cubic splines were used to determine BMI-specific GWG targets. The results showed that insufficient GWG was protective against cesarean delivery, large-for-gestational-age (LGA), and macrosomia but increased risks of preterm birth and congenital anomalies. Excessive GWG significantly elevated risks of preeclampsia, LGA, macrosomia, and neonatal hypoglycemia, while protecting against small-for-gestational-age (SGA). Using interquartile range method, we identified GWG ranges for normal-weight, overweight, and obese women were 7.0-12.5 kg, 5.0-11.0 kg, and 4.0-11.2 kg, respectively. Restricted cubic splines suggested relaxing the lower limit to 6 kg for normal BMI but showed risks below 1.8 kg. For overweight and obese women, GWG below guideline limits was beneficial. The current GWG guidelines may not fully suit T2DM pregnancies, particularly for overweight and obese women, highlighting the need for BMI-specific recommendations to optimize maternal and neonatal outcomes.